2003
DOI: 10.1029/2002jd003202
|View full text |Cite
|
Sign up to set email alerts
|

Use of dual‐frequency microwave links for measuring path‐averaged rainfall

Abstract: [1] Results are presented from an experiment designed to test the use of dual-frequency microwave attenuation for measuring path-averaged rainfall. In general, the relation between attenuation and path-averaged rainfall is nonlinear. However, for carefully chosen pairs of frequencies, the relation between the difference in attenuations and path-averaged rainfall is well represented by a straight line through the origin. The slope of this line is essentially unaffected by variations in the (unknown) drop size d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 18 publications
2
69
1
1
Order By: Relevance
“…The active approach is to use the SNMP to collect RSL measurements dedicated for weather monitoring. A recent publication details this methodology, and establishes a set of open-source tools which can be used to actively access the CMLs of main manufacturers, and receive the instantaneous RSL (and TSL) samples [9]. With this approach, RSLs (and TSLs) are available in real time as instantaneous samples, at sampling intervals that can be as small as 10 s. Note that to avoid unnecessary traffic load for the cellular provider, the active approach also requires adding a designated server for handling the RSL measurements.…”
Section: The Active Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The active approach is to use the SNMP to collect RSL measurements dedicated for weather monitoring. A recent publication details this methodology, and establishes a set of open-source tools which can be used to actively access the CMLs of main manufacturers, and receive the instantaneous RSL (and TSL) samples [9]. With this approach, RSLs (and TSLs) are available in real time as instantaneous samples, at sampling intervals that can be as small as 10 s. Note that to avoid unnecessary traffic load for the cellular provider, the active approach also requires adding a designated server for handling the RSL measurements.…”
Section: The Active Approachmentioning
confidence: 99%
“…In 2006, Messer et al [8] first demonstrated the idea of taking advantage of the existing, widely spread, cellular communication technology, and used the MLs, which are part of its backhaul network, for environmental monitoring. While the relation (1) still forms the basis of links (CMLs) instead of dedicated MLs as in Reference [9], brings new opportunities, as well as challenges. The major opportunity is obvious: the availability of millions of potential virtual meteorological sensors almost everywhere on Earth, with no costs for installation, maintenance, or communication.…”
Section: Introductionmentioning
confidence: 99%
“…Each dot represents a single 30-s disdrometer measurement (not path-averaged). 40 Only data points that were characterized as liquid precipitation by the Parsivel algorithm and where precipitation intensity was Atmos. Meas.…”
Section: Attenuation-rainfall Intensity Relationshipmentioning
confidence: 99%
“…Liebe et al (1989) and David et al (2013). 40 However, it is debatable whether the underlying cause is the wetting of the antennas or the attenuation by the fog droplets themselves. Observation of the accompanying time-lapse camera footage (Fig.…”
Section: Dew and Fogmentioning
confidence: 99%
“…Weather radar does not directly measure rainfall, but instead measures reflected energy using electromagnetic waves, which scan hundreds of meters above the Earth's surface (i.e., 1 or 2 km of altitude at 100 km) with its volume scan increasing with the square of its distance from the weather radar. The reflected energy may also be due to obstructions from the local topography [2]. Therefore, weather radar often encounters errors when observing near-surface rainfall.…”
Section: Introductionmentioning
confidence: 99%